Biochemical versus radiological screening for osteoporosis in menopause; will Irisin help? - Wisam Akram; Alaa Ibrahim Ali; Hind Hadi Majeed (Journal of the Pakistan Medical Association, 2024)
Objective: To verify the discriminative power of irisin in osteoporosis patients. Method: The comparative case-control study was conducted at the University Teaching Hospital, Baghdad, Iraq,from March 2020 to June 2021 after approval from the ethics review committee of the College of Medicine, Mustansiriyah University, Baghdad, and comprised post-menopausal women. After being scanned by dual-energyX-ray absorptiometer, the subjects were divided into groups based on T-scores; healthy controls with T-score >-1in group 1, and osteoporosis patients with T-score Less than -2.5 in group 2. Participants’ sera were tested for Irisin, 25-hydroxy vitamin D, and carboxyl-terminal telopeptides of type I collagen levels. T-score and bone mineral densitywere recorded as radiological markers. Correlation of irisin was determined with T-score and bone mineral density,cut-off value for serum irisin was worked out for osteoporosis prediction. Data was analysed using Medcalic 17. Result: Of the 142 women, 71(50%) were in group 1 with mean age 58.4±3.5 years, and 71(50%) were in group 2with mean age 58.7±3.4 years (p=0.87). Levels of irisin, 25-hydroxy vitamin D, carboxyl-terminal telopeptides of typeI collagen, bone mineral density and T-scores were significant between the groups (p<0.001). Serum irisin correlateddirectly with bone mineral density (r=0.97, p<0.001) and inversely with T-score (r= -0.95, p<0.001). The cut-off valueof serum irisin was 31.4ng/ml with 84% sensitivity and 100% specificity (p<0.001). Conclusion: Strong serum irisin correlation to osteoporosis radiological markers and its good discrimination ofosteoporosis implied its utility as a good serological marker of osteoporosis. Key Words: Bone Density, Fibronectins, Collagen, Post menopause, X-Rays, Osteoporosis, Vitamin D